Navigating Complexities: African Union's Peace and Security Strategy Challenges after Niger and Gabon Coups - Elamin, Mustafa Osman I. (International Journal of Membrane Science and Technology, 2023)
This study examines the intricate challenges that the African Union (AU) confronts in its pursuit of effective peace and security strategies following recent coup incidents in Niger and the ongoing situation in Gabon. The research analyzes the complex dynamics surrounding coup attempts, exploring their ramifications for regional stability, rising political intolerance, internally displaced populations, intricate government structures, enduring colonial legacies, and the emergence of global threats. Employing content analysis, the research draws from a diverse range of sources, including published and unpublished materials and references to news outlets. The study also compares coup scenarios in Niger and Gabon with similar instances globally to shed light on the multi-dimensional challenges that the AU faces. This research highlights historical factors, such as colonialism, that underpin coup occurrences and broader governance issues. It underscores the connection between persistent insecurity, hindered economic growth, exclusionary economic governance, and low development indicators, all contributing to an elevated risk of coup occurrences across Africa. The primary goal of this study is to contribute to a deeper understanding of the AU's evolving peace and security landscape and to offer recommendations aimed at bolstering its strategies for achieving lasting peace and security.